Homocysteine levels associate with subtle changes in leukocyte DNA methylation: an epigenome-wide analysis. (November 2017) - Mandaviya, Pooja R; Aïssi, Dylan; Dekkers, Koen F; Joehanes, Roby; Kasela, Silva; Truong, Vinh; Stolk, Lisette; Heemst, Diana van; Ikram, M Arfan; Lindemans, Jan; Slagboom, P Eline; Trégouët, David-Alexandre; et al.
Aim: Homocysteine (Hcy) is a sensitive marker of one-carbon metabolism. Higher Hcy levels have been associated with global DNA hypomethylation. We investigated the association between plasma Hcy and epigenome-wide DNA methylation in leukocytes.Methods: Methylation was measured using Illumina 450 k arrays in 2035 individuals from six cohorts. Hcy-associated differentially methylated positions and regions were identified using meta-analysis.Results: Three differentially methylated positions cg21607669 ( SLC27A1 ), cg26382848 ( AJUBA ) and cg10701000 ( KCNMA1 ) at chromosome 19, 14 and 10, respectively, were significantly associated with Hcy. In addition, we identified 68 Hcy-associated differentially methylated regions, the most significant of which was a 1.8-kb spanning domain ( TNXB/ATF6B ) at chromosome 6.Conclusion: We identified novel epigenetic loci associated with Hcy levels, of which specific role needs to be further validated.